Effects of Transporting Tapioca Products on Sediment Quality Offshore of Sriracha Bay, Chonburi Province, Thailand - Rakseree, Saranya; Intacharoen, Prasarn; Gunboa, Vichaya; Buranapratheprat, Anukul (Journal of Fisheries and Environment, 2024)
Transporting tapioca starch in coastal areas leads to dust dispersion, contributing to pollution in Sriracha Bay, Chonburi Province, Thailand. This pollution poses a threat to marine life, highlighting the need for monitoring to prevent environmental harm. To address this issue, sediment samples were collected from 16 locations in Sriracha during both the dry season (March 2020) and the rainy season (August 2020). The study aimed to examine variations in organic matter, a byproduct of tapioca dust transportation, over time. Analysis revealed that silty-clay sediments predominated in the area. During the dry season, sedimentary parameters such as total organic matter (TOM) (8.72±3.21%) and hydrogen sulfide (0.03±0.02 mg Sg-1), were notably high. In contrast, the rainy season revealed elevated water content, carbon, sulphur (53.59±14.48%, 2.31±0.22 mgg-1 and 0.16±0.12 mgg-1, respectively) and higher nutrient levels in pore water, including ammonia, nitrite and total nitrogen (18.12±4.11, 0.14±0.09 and 121.27±31.77 mg NL-1, respectively). Organic matter in the sediment was particularly concentrated in the northeast region, where tapioca starch was loaded onto ships, coinciding with relatively acidic conditions. These areas showed higher levels of TOM (11.30 –15.91%), especially during the dry season. The study advocates for dust management during tapioca starch transshipment as a crucial measure to mitigate the rise in TOM and hydrogen sulfide, which could jeopardize the marine ecosystem.